A REVIEW OF DESTRUCTIVE AND NON DESTRUCTIVE TESTING OF ALUMINUM AND ALUMINUM ALLOY PLATE OF TIG WELDING METHODS - E, Manigandan.; S., Sureshkumar (International Journal of Psychosocial Rehabilitation, 2020)
This paper reviews and deals with the welded quality of aluminum and aluminum alloy plates by the TIG welding method. The TIG welding method is one of the most used and popular methods to weld aluminum. Aluminum has unique properties: ductile, non-magnetic, light weight, weldability, and also has corrosion resistance in nature. Input parameters were varied according to the experimental design. The accuracy and quality of welded joints largely depend upon the type of inert gas, welding speed, and type of power supply. The mechanical properties of weld joints also vary based on the parameters. The mechanical properties of YS and UTS vary by pulsed and non-pulsed current at different frequencies. It has wide application in industry fields, namely marine, aircraft, heat exchangers, automobiles, oil refineries, etc.